2017
DOI: 10.1186/s12859-017-1514-2
|View full text |Cite
|
Sign up to set email alerts
|

DISMS2: A flexible algorithm for direct proteome- wide distance calculation of LC-MS/MS runs

Abstract: BackgroundThe classification of samples on a molecular level has manifold applications, from patient classification regarding cancer treatment to phylogenetics for identifying evolutionary relationships between species. Modern methods employ the alignment of DNA or amino acid sequences, mostly not genome-wide but only on selected parts of the genome. Recently proteomics-based approaches have become popular. An established method for the identification of peptides and proteins is liquid chromatography-tandem ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…Multidimensional scaling (MDS; Gower, 1966) was used to visualise the similarity of observations (Figure 5) and confirmed that the Havnø set and the freshwater reference unionoids display the higher degree of proteome similarity, while the samples from Hornstaad and PesB fall in a different area of the plot from each other and from the marine reference shells. The results were also in accordance with those obtained from another database-independent approach Appendix 1—figure 25, based on direct product ion spectra comparison (Rieder et al, 2017), which was adapted for this study (Appendix 1, section 3.6). Overall, our study, which represents one of the few that attempts to compare molluscan proteomes within the same clade (genus, family or order), shows that unionoid shells exhibit very similar proteome profiles, sharing many sequences between species Appendix 1—figure 23.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Multidimensional scaling (MDS; Gower, 1966) was used to visualise the similarity of observations (Figure 5) and confirmed that the Havnø set and the freshwater reference unionoids display the higher degree of proteome similarity, while the samples from Hornstaad and PesB fall in a different area of the plot from each other and from the marine reference shells. The results were also in accordance with those obtained from another database-independent approach Appendix 1—figure 25, based on direct product ion spectra comparison (Rieder et al, 2017), which was adapted for this study (Appendix 1, section 3.6). Overall, our study, which represents one of the few that attempts to compare molluscan proteomes within the same clade (genus, family or order), shows that unionoid shells exhibit very similar proteome profiles, sharing many sequences between species Appendix 1—figure 23.…”
Section: Resultssupporting
confidence: 86%
“…However, database-dependant search algorithms of DNA and/or protein sequences cannot take into account peptides and proteins that do not yet exist in databases. In recent years, as shotgun proteomics has become a routine tool for biochemistry, and huge amounts of data have been generated on novel systems and organisms (including extinct), there has been an increasing interest in developing methods enabling to compare proteome-wide measurements that would be flexible and allow database-free workflows (Palmblad and Deelder, 2012; Rieder et al, 2017; Yılmaz et al, 2016).…”
Section: ​1​ Archaeological Sites and Double-buttonsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further assess the effective distinctness of morph-specific spots, a pairwise spectrum-to-spectrum comparison was performed 154156 . The set of spectra from each MS run was compared to all the others belonging to a different morph, and the cosine distance computed 155 . The minimum of this distances for each spot (minimum non-self-distance) was retained and compared to the one computed between each spot and itself (self-distance).…”
Section: Methodsmentioning
confidence: 99%
“…Geographic distances between springs were calculated based on longitude and latitude of springs using package geosphere v.1.5.10 66 and the implemented function distm (Vincentry great circle distances). Pairwise spectrum distances (cosine distances) between MS/MS runs (proteome-wide distances independent of peptide-identification and therefore of the homology-based protein database) were computed in R using the DISMS2 algorithm 67 .…”
Section: Protein Identificationmentioning
confidence: 99%